The Application of Sequencing (Tartib) to Determine the Validity of Personal Financing Tawarruq Contracts: A Study in Selected Islamic Financial Institutions in Malaysia - Muhd Aiman Hakim Bin Zaharudin (Universiti Sains Islam Malaysia, 2024)
Matric: 3211412 (FSU)-Restricted until November 2026